A Pesquisa Crítica De Colaboração Na Formação De Profissionais Da Psicologia: Ressignificação Da Prática Institucional E Clínica Com Deficientes Intelectuais A Partir Da Obra Fundamentos Da Defectologia, De Vygotsky - Souza, Janaina Peripolli [UNIFESP] (2017)
This work seeks to critically analyze some psychological actions implemented in an institution for long permanence (nursing home) for the intellectually disabled. By using the Critical Collaborative Research (PCCOL) (Magalhães, 2006, 2011), the research aimed to look into the possibility of re-signification or transformation of the senses and meanings of a team of psychologists that work in the institution about the notion of disability. The theoretical framework is based on the Social-Cultural Historical Psychology, especially on Fundaments of Defectology (Vygotsky [1924 – 1943]/ 1997) mainly on concepts such as compensation, development, notion of subject, mediation, zone of proximal development, among others. Data production consisted mainly of audio recordings of the meetings with the group of participants about their practice in the institution under the light of the aforementioned framework. These recordings were transcribed, and the analysis and discussion of the data were carried out by looking at excerpts of transcriptions that answered the following research questions: By means of the reading and discussion of Vygotsky’s work, is it possible to notice the production of new senses and meanings in the practice and in the discourse of psychologist who have been work in a long–term institution for the intellectually disabled. In the excerpts produced, it was possible to see transformations in meanings regarding the abovementioned concepts brought by Vygotsky. As proposed the critical collaborative research, one can conclude that the locus of education, the sharing of ideas, the challenging of ideas, the critical position in the face of reality have resulted in the transformation of the practice of those professionals participating in the research.